Conversations with colleagues : on becoming an American Jewish historian - Gurock, Jeffrey S., 1949- (North American Jewish studies., 2018)
Sixteen senior scholars of American Jewish history - among the men and women whose work and advocacy have moved their discipline into the mainstream of academia - converse on the intellectual and personal roads they have traveled in becoming leaders in their areas of expertise. Through their thoughtful and candid recollections of the challenges they faced becoming accepted academics, they retell the story of how the study of the Jews and Judaism in the United States rose from being long dismissed as an amateurish enterprise not worthy of serious consideration in the world of ideas to its position today as a respected field in communication with all humanities scholars. They also imagine and chart the direction the writing on American Jews will take in the coming era.